A Cognitive Pragmatic Review of the Metaphorical Expressions in Indonesian Online Ads as a Basis for Language Learning in Elementary Schools - Wibowo, Setiawan Edi; Sekarsari, Endah Harum (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
The importance of teaching language to children underlies the birth of this study. Therefore, this study aims to describe the metaphorical form of online advertising discourse in Indonesia as a basis for teaching language in elementary schools. This research employs a qualitative descriptive study. Data are collected through non-participant observation and note-taking techniques. The data in this study are sentences that contain A Cognitive Pragmatic Review on The Metaphorical Expression of Indonesian Online Ads. Meanwhile, the source of data in this research is YouTube. The object of this research is Metaphorical Expression and the subject in this study is Indonesian Online Ads. The data collection technique used in this study is the Listening and Recording Technique. Meanwhile, the data analysis technique uses padan and agih techniques with using referential and pragmatics to show and compare the referent or the meaning of the source and the metaphorical expression of the target. The method is combined with a reflective-introspective to show how cognitive processes manage to produce a speech. Besides, the inductive inference technique shows the correspondence between the source and target concepts. The expression is metaphorically constructed based on the correspondence between the source and the target domain. Indonesian online advertisement is generally constructed with structural, orientational, and ontological metaphors. The metaphor of Indonesian online advertisement pragmatically functions as assertive information, directive invitation, and expression of wonder with a structural, lexical, and counter-factual presupposition. Meanwhile, the conceptual strategy is associative.